Glacial-Interglacial Variations in Organic Carbon Burial in the Northwest Pacific Ocean Over the Last 380 kyr and its Environmental Implications - Zhang, Yuying; Hu, Limin; Wu, Yonghua; Dong, Zhi; Yao, Zhengquan; Gong, Xun; Liu, Yanguang; Ikehara, Minoru; Shi, Xuefa (Frontiers in Earth Science, 2022)
The carbon cycle on the Earth’s surface is linked to long-term variations in atmospheric CO2 as well as carbon sequestration in various pools. The burial of particulate organic carbon (OC) in marine sediments is also highly sensitive to the global climate over geological time scales, but with little known about OC burial and its regulations over glacial-interglacial cycles. Here, we present a long-term OC record over the past ~380 kyr, from the Northwest Pacific Ocean, an ideal region for studying OC burial and its environmental implications on glacial-interglacial timescales. We observed a distinct cyclicity of higher OC burial in glacial periods, which was coupled with input from Asian dust and the Kuroshio Current but seemingly decoupled from biogenic element contents, implying a limited effect of marine productivity on OC burial. Moreover, the sedimentary record of OC was synchronous with oceanic redox conditions, especially the redox sensitive elements at the sediment-water interface, indicating a relatively reducing conditions that enhanced OC preservation during glacial periods. The overall glacial-interglacial OC burial regime in the Northwest Pacific Ocean was conceptually constructed. It showed a higher efficiency of OC burial during glacial periods and significant degradation during interglacial periods. The findings of this study highlighted the important contribution of better preservation controls under relatively reducing state on OC burial, demonstrating the sensitivity of the carbon cycle to global climate on orbital scale.